Ulama dan Jawara: Studi tentang Persepsi Ulama terhadap Jawara di Menes Banten Selatan - karomani karomani (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
Ulama (religious leader) and jawara (gank leader) become prominent local elites in Menes,South Banten. Long history of those two leaders resulted in amalgamation of both elites:alongside with pure ulama, there is also a group of ulama who is also jawara. Both eliteshave positive perception to each other. Jawara-ulama was perceived by ulama as figures who develop, maintain and preserve Banten cultural art. Jawaras are loyal to ulama and protect ulama as well. On the other hand, jawara from outside of ulama group was negatively perceived, assuming bad habits such as disobedience toward religious principles, bandit, doing many violence act. The perception of ulama toward jawara was affected by a closeness in terms of relationship with jawara, a resemblance of beliefs, values, worldview, religious understanding, prejudice and life experience.